Benefits of Older Volunteering on Wellbeing: An International Comparison - Gil-Lacruz, Marta; Saz-Gil, María I.; Gil-Lacruz, Ana I. (Frontiers in Psychology, 2019)
Healthier aging implies lower health service expenditure and the possibility for individuals to make a longer and more valuable contribution society. Lifestyles, including volunteering, affect our health. The policy implications of the present study aim to broaden the state of knowledge and be useful to public decision-makers: If voluntary activities enhance the integration of older people into society, their participation will help to generate economic resources and improve their own welfare. If, however, health and participation do not show positive synergies, then policy makers must act independently in each of these fields. In this work we focus on the societies of Chile, Mexico and Spain because they have a significantly aging population, share common traits but also exhibit important differences. The empirical study employs micro-data from the World Value Survey (1994-1998; 2005-2009 and 2010-2014) and macro-data from the statistics of OECD (Organization for Economic Co-operation and Development). Micro and macro-data are crossed by national and temporal identifiers. Our main results provide empirical evidence that volunteering might improve any indicator of wellbeing except happiness. Different kind of activities has different impact on individual wellbeing. For example, volunteering in activities related to social awareness is positive for male life satisfaction, whereas volunteering in activities related to religious issues is positive for male life satisfaction, but also female happiness. In general, voluntary activities have a stronger impact on male wellbeing than female wellbeing.